Suicidal ideation among medical students, burnout or depression? Maybe both. - VALE, THAÍS CAMPELO BEDÊ; ARAÚJO, LÍVIA RODRIGUES DE; MEDEIROS, VITÓRIA NUNES; PAIVA, JOSÉ HÍCARO HELLANO GONÇALVES LIMA; BACHUR, TATIANA PASCHOALETTE RODRIGUES; CASTRO, DANIEL BEZERRA DE (Revista Brasileira de Educação e Saúde, 2021)
Depression is a common mental condition worldwide and a major cause of debility, with the potential to impair the quality of life of affected people. Medical students are more likely to develop psychiatric disorders, with depression, anxiety, and burnout being the most common ones. The aim of this study was to investigate the prevalence of depressive symptoms in medical students and their association with burnout and aspects of life. This is an analytical cross-sectional study. Data collection was performed using four validated scales and a questionnaire in 511 medical students from the first to the fourth year from different universities. Depression was present in 49% of the students. A correlation was found between depression and female gender. Regarding the students' daily sleep time, 54.5% of the students slept only 3 to 6 hours per night. The use of psychoactive substances was reported by 29.9%. Regarding the emotional support offered by universities, about 92.8% of students with depressive symptoms reported not receiving adequate emotional support. As for quality of life, all domains were impaired among students with depression. According to the two-dimensional criterion, 37% of the students have burnout, with correlation between the presence of the syndrome and depressive symptoms. In addition, burnout proved to be an independent risk factor for suicidal ideation and self-mutilation. New methods that can help detect and address factors that trigger stress and depressive symptoms in medical students are needed to reduce the incidence of depression.